Positive electrode material, positive electrode plate and secondary battery

By controlling the unit cell volume and unit cell parameters of the positive electrode material, and controlling the content of free nitrate ions in the material, a stable interface protection layer is formed, the problem of insufficient performance of the existing lithium-ion battery positive electrode materials is solved, and higher capacity, magnification and cycling stability are achieved.

CN119650686APending Publication Date: 2025-03-18SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411976470.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The capacity, magnification and cycle stability of the positive electrode materials of existing lithium-ion batteries are poor, which limits the improvement of the battery's performance.

Method used

By controlling the unit cell volume and unit cell parameters of the positive electrode material, and controlling the content of free nitrate ions in the material, a stable interface protective layer is formed to reduce the side reaction between the electrolyte and the surface of the positive electrode material.

Benefits of technology

The structural stability of the positive electrode material is improved and the capacity, magnification and cycle stability of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650686A_ABST
    Figure CN119650686A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a positive electrode plate and a secondary battery. The crystal of the positive electrode material meets the following conditions: the unit cell volume V is less than 102.3, the unit cell parameter a is less than or equal to 2.8790, and the unit cell parameter c is less than or equal to 14.2550; the content of free nitrate ions in the positive electrode material is N1, wherein N1 is more than or equal to 10ppm and less than or equal to 100ppm. By controlling the unit cell volume of the positive electrode material and the content of free nitrate ions in the material to be within the range, the structural stability of the positive electrode material can be improved, and meanwhile, the capacity, the rate and the cycling stability of a battery prepared from the positive electrode material can also be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art

[0002] Lithium-ion batteries (LIBs) are widely used in 3C electronic products, electric vehicles, energy storage and other fields. As the core component of lithium-ion batteries, cathode materials directly determine the operating voltage and storage capacity of the battery. However, the current cathode materials have poor capacity, rate and cycle stability, which restricts the development of cathode materials. Summary of the invention

[0003] In view of this, in order to solve at least one of the above defects, it is necessary to provide a positive electrode material.

[0004] In addition, it is also necessary to provide a positive electrode sheet and a secondary battery using the above-mentioned positive electrode material.

[0005] In a first aspect, the present invention provides a positive electrode material, wherein the unit cell volume V of the positive electrode material is less than 102.3 Å. 3 , the unit cell parameters of the positive electrode material are a≤2.8790 Å, c≤14.2550 Å; the content of free nitrate ions in the positive electrode material is N1, wherein 10ppm≤N1≤100ppm.

[0006] In some possible embodiments, the content of free lithium ions in the positive electrode material is N2, wherein 300ppm≤N2≤450ppm.

[0007] In some possible embodiments, the content N1 of free nitrate ions is 40ppm~70ppm.

[0008] In some possible embodiments, the unit cell volume satisfies: 101.448 Å 3 <V<102.3 Å 3 , the unit cell parameters satisfy: 2.8737 Å≤a≤2.8790 Å; 14.1855 Å≤c≤14.2550 Å.

[0009] In some possible embodiments, the general formula of the positive electrode material is as follows: Li x Ni a Co b M c N dO2, M includes at least one of Mn and Al, and the N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Sn, Mo, W, Sb, Ta, Sn, Ga and Y, wherein 0.98≤x≤1.1, 0.50≤a≤0.70, 0.06≤b≤0.12, 0.20<c≤0.32, 0<d≤0.10, a+b+c+d=1.

[0010] In some possible embodiments, a cross-section of the positive electrode material is observed with a scanning electron microscope, and 10 points are randomly selected from the cross-section of the positive electrode material for EDS point scanning to test the Ni, Co, and Mn contents. In the EDS spectrum results of the positive electrode material, the standard deviation of the mass content of each element Ni, Co, and Mn in the positive electrode material is 0.001~0.03.

[0011] In some possible embodiments, the volume median particle size D50 of the positive electrode material is 3.5 μm to 4.1 μm.

[0012] In some possible embodiments, the specific surface area of ​​the positive electrode material is 0.7 m 2 / g ~1.0 m 2 / g.

[0013] In some possible embodiments, the tap density ρ1 of the positive electrode material is 1.8-2.2 g / cm 3 .

[0014] In some possible embodiments, the powder compaction density ρ2 of the positive electrode material is 3.00-3.50 g / cm 3 .

[0015] In some possible embodiments, the positive electrode material is a single crystal positive electrode material, and the average particle size of primary particles of the positive electrode material is 1 μm to 5 μm.

[0016] In a second aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above.

[0017] In a third aspect, an embodiment of the present application provides a secondary battery, comprising an electrode assembly, wherein the electrode assembly comprises a positive electrode material, a separator and a negative electrode plate, wherein the separator is arranged between the positive electrode plate and the negative electrode plate, and the positive electrode plate comprises the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above.

[0018] The positive electrode material provided in the embodiment of the present application controls the unit cell volume V of the positive electrode material to be less than 102.3 Å. 3 , unit cell parameters a≤2.8790 Å, c≤14.2550 Å, and at the same time controlling the content of free nitrate ions to satisfy 10ppm≤N1≤100ppm, while improving the structural stability of the positive electrode material, being able to form a stable interface protection layer on the surface of the positive electrode material, reducing the side reactions between the electrolyte and the surface of the positive electrode material, thereby comprehensively improving the capacity, rate and cycle stability of the battery prepared using the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.

[0020] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.

[0021] Figure 3 This is the Li element spectrum obtained by XPS characterization of the positive electrode material of Example 1 after the first charge and discharge.

[0022] Figure 4 This is the Li element spectrum obtained by XPS characterization of the positive electrode material prepared in Comparative Example 2 after the first charge and discharge. DETAILED DESCRIPTION

[0023] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0024] The present application provides a positive electrode material, wherein the unit cell volume V of the positive electrode material is less than 102.3 Å. 3 , the unit cell parameters of the positive electrode material are a≤2.8790 Å, c≤14.2550 Å; in addition, the content of free nitrate ions in the positive electrode material is N1, wherein 10ppm≤N1≤100ppm.

[0025] The present application controls the unit cell volume V of the positive electrode material to be less than 102.3 Å3, the unit cell parameters a≤2.8790 Å, c≤14.2550 Å, and the content of free nitrate ions to satisfy 10ppm≤N1≤100ppm. While improving the structural stability of the positive electrode material, a stable interface protection layer can be formed on the surface of the positive electrode material to reduce the side reactions between the electrolyte and the surface of the positive electrode material, thereby comprehensively improving the capacity, rate and cycle stability of the battery prepared using the positive electrode material.

[0026] Specifically, the present application firstly controls the unit cell volume V of the cathode material to be less than 102.3 Å. 3 , unit cell parameters a≤2.8790 Å, c≤14.2550 Å, which is conducive to stabilizing the crystal structure, and the distance between atoms or ions in the unit cell is short, so that the interaction force between atoms or ions (such as Coulomb force, van der Waals force, etc.) is enhanced, thereby increasing the cohesive energy of the crystal, thereby reducing the volume change of the positive electrode material during the charge and discharge process, and reducing the generation and diffusion of microcracks in the crystal; and then by controlling the content of free nitrate ions in the positive electrode material to meet 10ppm≤N1≤100ppm, the presence of an appropriate amount of free nitrate ions in the positive electrode material is conducive to inhibiting the volume change of the positive electrode material during the charge and discharge process. The inventor speculates that this is because the free nitrate ions in the positive electrode material will induce the formation of a Li2O stable interface protection layer (CEI film) on the surface of the positive electrode material during the first charge and discharge process, thereby achieving the effect of inhibiting the volume change of the positive electrode material during the charge and discharge process, thereby further improving the rate and cycle stability of the positive electrode material.

[0027] When the unit cell volume V of the positive electrode material is ≥102.3Å3, the strength and toughness of the lattice will be reduced, making it easy for the material to have lattice defects when subjected to alternating stress, causing microcracks in the crystal, which may become sensitive points for electrochemical corrosion, increase the probability of side reactions with the electrolyte, and affect the cycle life of the battery. For the above positive electrode material, the unit cell volume further satisfies: 101.448 Å 3 <V<102.3 Å 3 , the unit cell parameters further satisfy: 2.8737 Å≤a≤2.8790 Å; 14.1855 Å≤c≤14.2550 Å.

[0028] Furthermore, the unit cell volume of the cathode material is 101.448 Å 3 <V<102.295Å 3 , unit cell parameters 2.8737 Å≤a≤2.8780 Å, 14.1855≤Å c≤14.2540 Å. By controlling the unit cell volume and unit cell parameters within the above range, the stability of the crystal structure can be further improved, thereby achieving further improvement in rate and cycle stability.

[0029] The present application controls the content of nitrate ions in the positive electrode material to be 10ppm≤N1≤100ppm, and can form a CEI film of suitable thickness and stability on the surface of the positive electrode material, and can also effectively isolate the electrolyte, reduce the occurrence of interface side reactions, and ensure that the battery has a high capacity and electrical performance, and reduce the internal resistance of the battery. The inventor speculates that the free nitrate ions in the positive electrode material will induce the formation of a Li2O stable interface protection layer (CEI film) on the surface of the positive electrode material during the first charge and discharge process. The specific reaction formula is: The protective layer has high chemical stability, can remain inert under high voltage, effectively isolate the electrolyte, and reduce the occurrence of interface side reactions. When the content of free nitrate ions is less than 10ppm, the reaction concentration of the interface protective layer cannot be reached, and the thickness and density of the CEI film may not meet the requirements for effective protection of the positive electrode. When the content of free nitrate ions is greater than 100ppm, more Li will be consumed. + , thereby reducing the capacity and electrical performance of the battery prepared using the positive electrode material, and generating a thicker CEI film, increasing the internal resistance of the battery, resulting in increased energy loss during the charge and discharge process of the battery, and reducing the efficiency of the battery.

[0030] Further, the content of free nitrate ions in the positive electrode material is 13ppm≤N1≤96ppm. Within this range, the formed CEI film can be further optimized, the occurrence of interfacial side reactions can be further reduced, and the impact on the capacity and electrical properties of the battery and the internal resistance of the battery can be further reduced. Exemplarily, the content of free nitrate ions can be 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm or any value within the range of any two of the above values.

[0031] Furthermore, the content of free nitrate ions in the positive electrode material is 40ppm≤N1≤70ppm. Within this range, the formed CEI film can be further optimized, the occurrence of interfacial side reactions can be further reduced, and the impact on the battery capacity and electrical performance as well as the battery internal resistance can be further reduced.

[0032] In some embodiments, the content of free lithium ions in the positive electrode material is 300ppm~450ppm. The positive electrode material has an appropriate amount of free lithium ions, which can form an effective and appropriately thick Li2O stable interface protection layer under the induction of free nitrate, effectively isolate the electrolyte, reduce the occurrence of interface side reactions, and ensure that the prepared battery has a high capacity and electrical performance. Exemplarily, the content of free lithium ions in the positive electrode material can be 300ppm, 310ppm, 320ppm, 330ppm, 340ppm, 350ppm, 360ppm, 370ppm, 380ppm, 390ppm, 400ppm, 410ppm, 420ppm, 430ppm, 440ppm, 450ppm or any value within the range formed by any two of the above values.

[0033] In some embodiments, the volume median particle size D50 of the positive electrode material can be 3.5μm~4.1μm. The median particle size D50 represents the particle size of the material particles corresponding to the cumulative particle size distribution percentage reaching 50% volume ratio. In this application, by controlling the median particle size of the positive electrode material within the above appropriate range, the positive electrode material particles formed are of moderate size, which is conducive to reducing the specific surface area of ​​the particles and reducing the side reactions between the particles and the electrolyte, thereby further improving the safety and cycle life of the material; at the same time, the positive electrode material particles of the above range size are also conducive to reducing the internal stress of the particles and reducing the risk of electrochemical polarization of lithium ions inside and outside the particles, thereby increasing the capacity of the battery prepared using the positive electrode material. Exemplarily, the median particle size D50 can be 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4.0μm, 4.1μm or any value within the range composed of any two of the above values.

[0034] In some embodiments, the specific surface area of ​​the positive electrode material is in the range of 0.7 m 2 / g~1.0 m 2 / g, the specific surface area of ​​the positive electrode material is appropriate, which is conducive to reducing the direct contact between the positive electrode material and the electrolyte, thereby reducing the generation of side reactions, and is conducive to improving the cycle performance of the battery prepared with the positive electrode material, while also ensuring that the battery prepared with the positive electrode material has good rate performance. For example, the specific surface area of ​​the positive electrode material can be 0.7 m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0 m 2 / g or any value within the range formed by any two of the above values.

[0035] In some embodiments, the tap density ρ1 of the positive electrode material is 1.8-2.2 g / cm 3The positive electrode material has a relatively high tap density, which is beneficial to improving the compaction of the electrode sheet containing the positive electrode material, and is beneficial to improving the capacity of the battery prepared by using the positive electrode material.

[0036] In some embodiments, the powder compaction density ρ2 of the positive electrode material is 3.00~3.50 g / cm 3 The positive electrode material has a high powder compaction density, so that the positive electrode material can have a high compaction density when it is made into a pole piece, so as to improve the capacity of the positive electrode material.

[0037] Specifically, the general formula of the positive electrode material in the embodiment of the present application is as follows: Li x Ni a Co b M c N d O2, M includes at least one of Mn and Al, N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Sn, Mo, W, Sb, Ta, Sn, Ga and Y, wherein 0.98≤x≤1.1, 0.50≤a≤0.70, 0.06≤b≤0.12, 0.20<c≤0.32, 0<d≤0.10, a+b+c+d=1. By doping the ternary positive electrode material with elements, the crystal structure of the positive electrode material can be optimized and the stability of the crystal structure can be further improved. It can also further improve the structural stability and conductivity of the positive electrode material.

[0038] Among them, the value of x can be specifically 0.98, 0.99, 1.0, 1.02, 1.04, 1.05, 1.07, 1.08, 1.09 or 1.1, the value of a can be specifically 0.5, 0.6, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.7, etc., the value of b can be 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, etc., and the value of c can be 0.20, 0.21, 022, 0.23, 0.25, 0.26, 0.27, 0.28, 0.29 or 0.32, etc., and are not limited here. The value of d can be 0.02, 0.03, 0.04, 0.05, 0.07, 0.08, 0.09 or 0.10, etc.

[0039] In some embodiments, the N element may include at least one of high-valent elements such as W, Sn, Mo, Sb and Ga. By doping the positive electrode material with these high-valent elements, the crystal structure can be further stabilized, and the structural stability of the positive electrode material can be further improved.

[0040] The cross section of the positive electrode material is observed with a scanning electron microscope, and 10 points are randomly selected from the cross section of the positive electrode material for EDS point scanning to test the Ni, Co, and Mn contents. In the EDS spectrum results of the positive electrode material, the standard deviation of the mass content of each element of Ni, Co, and Mn in the positive electrode material is ≤0.03. This is conducive to the uniform distribution of Ni, Co, and Mn elements inside the positive electrode material and reduces the structural defects of the particles in the positive electrode material. In the positive electrode material, the smaller the standard deviation of the mass content of the aforementioned elements, the better. Further, the standard deviation of the mass content of each element of Ni, Co, and Mn in the positive electrode material is 0.001~0.03. Exemplarily, the standard deviation of the mass content of each element Ni, Co and Mn is 0.001, 0.003, 0.005, 0.007, 0.009, 0.01, 0.013, 0.015, 0.017, 0.019, 0.02, 0.023, 0.025, 0.027, 0.029, 0.03 or any value within the range formed by any two of the above values.

[0041] In some embodiments, the positive electrode material is a single crystal positive electrode material (or a quasi-single crystal material), that is, the smallest particle of the positive electrode material is a primary particle or a secondary particle formed by no more than five primary particles, wherein the average particle size of the primary particles is 1µm~5µm. By controlling the primary particle size of the positive electrode material within the above appropriate range, the primary particles formed are of moderate size, which is conducive to reducing the specific surface area of ​​the particles and reducing the side reactions between the particles and the electrolyte, thereby further improving the safety and cycle life of the material; moreover, the primary particles within the above particle size range can shorten the transmission path of lithium ions, which is conducive to improving the rate performance of the battery; in addition, the primary particles of the above range size are also conducive to reducing the internal stress of the particles and reducing the risk of electrochemical polarization of lithium ions inside and outside the particles, thereby increasing the capacity of the battery prepared using the positive electrode material. Exemplarily, the average particle size of the primary particles can be 1µm, 2µm, 3µm, 4µm, 5µm, or any value within the range composed of any two of the above values.

[0042] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nano-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more "single crystal morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles. For ease of understanding, the single crystal positive electrode material involved in this application can be understood as a positive electrode material particle containing a single grain with the same orientation, and the average particle size of the above single grain is 1μm~5μm.

[0043] It can be understood that a single grain in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particles" refer to those formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually between 1μm and 5μm. In general, the roundness of the particles of "quasi-secondary particles" is lower than that of the above-mentioned conventional "secondary particles".

[0044] It should be further explained that the "single crystal" in the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more of "single crystal-like morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles.

[0045] Based on the same inventive concept, the present application also provides a method for preparing the aforementioned positive electrode material, which specifically comprises the following steps: Step S1, annealing a hydroxide precursor in nitric acid to obtain an oxide precursor.

[0046] Specifically, the hydroxide precursor of the positive electrode material is placed in a nitric acid atmosphere and subjected to nitration annealing treatment to obtain an oxide precursor containing nitrate ions. The atmosphere of the nitration annealing treatment contains only HNO3 and H2O, and the O2 content in the atmosphere is less than 1.0 ppm.

[0047] In some embodiments, the concentration of nitric acid is 1% to 3%. For example, the concentration of nitric acid can be 1%, 2%, 3%, or any value within the range formed by any two of the above values. The through hole controls the concentration of nitric acid, and the retention amount of nitrate ions in the oxide precursor can be regulated, and then the content of free nitrate ions in the positive electrode material prepared by the precursor can be regulated to 10ppm to 100ppm, so as to meet the requirements of the above positive electrode material.

[0048] In some embodiments, the annealing temperature is 200°C to 800°C, the heating rate is 0.5°C / min to 3°C / min, and the annealing time is 3h to 10h. By controlling the annealing temperature and annealing time, the retention amount of nitrate ions in the oxide precursor can be regulated, and then the content of free nitrate ions in the positive electrode material prepared using the precursor can be regulated to 10ppm to 100ppm to meet the requirements of the aforementioned positive electrode material. Exemplarily, the annealing temperature can be 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, or any value within the range of any two of the above values. Exemplarily, the annealing time can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any two of the above values.

[0049] In some embodiments, the gas pressure of the reaction environment is controlled to be 2.0 kPa to 4.0 kPa (slightly lower than the saturated vapor pressure of nitric acid at the above concentration).

[0050] In some embodiments, the general formula of the hydroxide precursor of the positive electrode material is as follows: Ni a Co b M c (OH)2, wherein the M element includes at least one of Mn and Al, 0.50≤a≤0.70, 0.06≤b≤0.12, 0.20<c≤0.32, a+b+c=1.

[0051] Step S2, mixing the oxide precursor, lithium source and dopant and performing two-stage sintering to obtain a positive electrode material matrix.

[0052] Specifically, the obtained oxide precursor is mixed in a molar ratio (n (Ni+Co+Mn) :n Li =1:1) and lithium salt are preliminarily mixed, and an appropriate amount of dopant is added for uniform mixing. After that, the mixture is placed in an atmosphere furnace and sintered in two stages at a corresponding temperature and oxygen atmosphere. The two-stage sintering includes a first stage sintering and a second stage sintering performed in sequence. Sintering in an oxygen atmosphere can achieve the reaction of the material with oxygen to form a target layered compound.

[0053] Among them, the temperature of the first sintering stage is 400℃~800℃, and the sintering is carried out for 4~8h in the low temperature stage (400~800℃). This temperature stage mainly realizes the melting of lithium salt and the infiltration of auxiliary materials into the precursor. By adjusting the sintering temperature and sintering time of the low temperature stage, the lithium salt and auxiliary materials can be fully melted and fully infiltrated into the precursor to improve the uniformity of infiltration. The temperature of the first sintering stage can further be 500℃~750℃. For example, the temperature of the first sintering stage can be 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃ or any value within the range of any two of the above values. For example, the time of the first sintering stage can be 4h, 5h, 6h, 7h, 8h or any value within the range of any two of the above values.

[0054] The second stage of sintering is at a temperature of 800-1100°C. The sintering is carried out at the high temperature stage (800-1100°C) for 8-16 hours. This temperature stage is mainly for the grain formation and stabilization process. By regulating the temperature and sintering time of high temperature sintering, the unit cell size and unit cell parameters can be regulated. By controlling the sintering temperature and time within the above range, the unit cell volume V can be controlled to be less than 102.3 Å. 3 , unit cell parameters a≤2.8790 Å, c≤14.2550 Å, and the desired crystal is obtained. The temperature of the second sintering stage can further be 900°C~1000°C. For example, the temperature of the first sintering stage can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, or any value within the range of any two of the above values. For example, the time of the second sintering stage can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, or any value within the range of any two of the above values.

[0055] By setting up a two-stage platform sintering, it is possible to ensure that the crystal grows fully without over-sintering, thereby controlling the unit cell volume to meet the required standards, thereby improving the particle strength and structural stability.

[0056] In some embodiments, the dopant contains N element, and the N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Sn, Mo, W, Sb, Ta, Sn, Ga and Y. By doping the ternary positive electrode material with elements, the crystal structure of the positive electrode material can be optimized and the stability of the crystal structure can be further improved. The structural stability and conductivity of the positive electrode material can also be further improved.

[0057] In some embodiments, the N element may include at least one of high-valent elements such as W, Sn, Mo, Sb and Ga. By doping the positive electrode material with these high-valent elements, the crystal structure can be further stabilized, and the structural stability of the positive electrode material can be further improved.

[0058] In some embodiments, the lithium salt can be at least one of lithium hydroxide, lithium carbonate, and the like.

[0059] Step S3, crushing and coating the cathode material matrix to obtain the cathode material. The cathode material satisfies: unit cell volume V<102.3 Å 3 , unit cell parameters a≤2.8790 Å, c≤14.2550 Å; the content of free nitrate ions in the positive electrode material is N1, wherein 10ppm≤N1≤100ppm.

[0060] Specifically, the cathode material matrix is ​​air flow crushed, and then the crushed matrix is ​​uniformly mixed with the coating agent and sintered. This process is to improve the electrochemical performance of the cathode material by coating. After that, the coated cathode material is screened and demagnetized to obtain the finished cathode material.

[0061] The coating post-treatment in this step is mainly dry coating, the coating amount is small, and the formed coating layer is loose, which is convenient for the transmission of free nitrate ions and reduces the consumption of free nitrate ions in the coating process. Specifically, the coating method can be conventional dry coating.

[0062] In some embodiments, the coating treatment temperature is 450°C to 750°C, the time is 4h to 10h, and the sintering atmosphere can be an oxygen atmosphere. Exemplarily, the coating treatment temperature is 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, or any value within the range of any two of the above values. Exemplarily, the sintering time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any two of the above values.

[0063] In some embodiments, the coating element contained in the coating agent includes at least one of Al, Ti, Zr, Y, Co, W, La, Nb, and Mo.

[0064] In the present embodiment, a conventional hydroxide precursor is used for nitration pretreatment to obtain an oxide precursor containing nitrate ions, and the oxide precursor is doped with elements and the sintering process is regulated to control the unit cell volume V of the cathode material to be less than 102.3Å. 3 , the unit cell parameters a≤2.8790 Å, c≤14.2550 Å, and a positive electrode material with a stable crystal structure is obtained. The distance between atoms or ions in the unit cell is short, so that the interaction force between atoms or ions (such as Coulomb force, van der Waals force, etc.) is enhanced, thereby further improving the cohesive energy of the crystal, thereby reducing the volume change during the charge and discharge process, thereby improving the rate and cycle stability of the battery using the positive electrode material. At the same time, by controlling the content of free nitrate ions in the positive electrode material to 10ppm~100ppm, a Li2O stable interface protective layer will be induced to form on the surface of the positive electrode material. The protective layer has high chemical stability, can remain inert at high voltage, effectively isolate the electrolyte, and reduce the occurrence of side reactions. Therefore, under high voltage, the positive electrode material of the embodiment of the present application can effectively improve the capacity, rate and cycle stability of the prepared battery.

[0065] An embodiment of the present application also provides a positive electrode sheet using the aforementioned positive electrode material, comprising a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode material.

[0066] The positive electrode current collector may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0067] The present application also provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing. The electrode assembly includes a separator, a negative electrode sheet and the positive electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.

[0068] In some embodiments, the outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.

[0069] In some embodiments, the electrode assembly may be a laminated structure, which is formed by alternately stacking a positive electrode sheet, a separator, and a negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.

[0070] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be a composite current collector disclosed in any prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium-ion battery, a sodium-ion battery, a solid electrolyte battery, etc., without limitation herein.

[0071] like Figure 1 and Figure 2 As shown in the figure, they are schematic diagrams of lithium removal and lithium insertion during the charging and discharging process of a lithium-ion battery prepared by using the positive electrode material provided in the embodiment of the present application. Figure 1 As shown in , when a lithium-ion battery is charged, lithium ions are released from the positive electrode and embedded in the negative electrode; Figure 2 As shown, when a lithium-ion battery is discharged, lithium ions are released from the negative electrode and embedded back into the positive electrode.

[0072] In the embodiment of the present application, the unit cell volume V of the positive electrode material is controlled to be less than 102.3 Å. 3, the unit cell parameters a≤2.8790 Å, c≤14.2550 Å, which improves the stability of the crystal structure. The distance between atoms or ions in the unit cell is shorter, which enhances the interaction force between atoms or ions (such as Coulomb force, van der Waals force, etc.), thereby further improving the cohesive energy of the crystal, thereby reducing the volume change during the charge and discharge process, thereby improving the rate and cycle stability of the battery. At the same time, by controlling the residual nitrate ion content in the positive electrode material to 10ppm~100ppm, a Li2O stable interface protective layer will be induced to form on the surface of the positive electrode material. The protective layer has high chemical stability and can remain inert at high voltage, effectively isolate the electrolyte, and reduce the occurrence of side reactions. Therefore, under high voltage, the use of the aforementioned positive electrode material can effectively improve the capacity, rate and cycle stability of the battery. The aforementioned positive electrode material was used in button cells to evaluate the battery's cycle performance. At room temperature (25°C), the 1C / 0.1C rate was ≥87%, and after 50 cycles at 1C / 0.1C, the cycle retention rate was ≥97.1%, and the first efficiency was ≥88.4%. The use of the aforementioned positive electrode material on the surface can effectively improve the battery's rate and cycle performance.

[0073] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0074] Example 1 Step S1, the hydroxide precursor Ni 0.60 Co 0.10 Mn 0.30 (OH)2 is placed in a nitric acid atmosphere with a concentration of 2% and subjected to nitration annealing treatment to obtain an oxide precursor; the annealing temperature is 500°C, the heating rate is 1.5°C / min, and the holding time is 7h.

[0075] Step S2, weigh 500g of the above-mentioned oxide precursor, mix it evenly with 237.8g of lithium carbonate and 2.25g of WO3, and sinter the mixture in an oxygen atmosphere furnace to obtain a positive electrode material matrix; wherein, the sintering temperature of the first stage is 550°C, the sintering time is 6h, and the sintering temperature of the second stage is 920°C, and the sintering time is 12h.

[0076] Step S3, crush the positive electrode material matrix, weigh 300g of the crushed material and mix it evenly with 0.25g of TiO2, and place the mixture in an oxygen atmosphere furnace for sintering to obtain the positive electrode material; wherein the sintering temperature is 450°C and the sintering time is 8h. Since the content of the doping element in the embodiment of the present application is relatively low, it may not be reflected in the chemical formula of the positive electrode material, that is, the chemical formula of the positive electrode material can be expressed as LiNi 0.60 Co 0.10 Mn 0.30 O2. The chemical formula of the positive electrode material in the subsequent examples and comparative examples is the same.

[0077] Example 2 The difference from Example 1 is that in step S1, the concentration of nitric acid is 3%. The other steps are basically the same as those in Example 1, please refer to Example 1.

[0078] Example 3 The difference from Example 1 is that in step S1, the concentration of nitric acid is 1%. The other steps are basically the same as those in Example 1, please refer to Example 1.

[0079] Example 4 The difference from Example 1 is that in step S1, the annealing temperature during the nitration process is 200° C. The other steps are basically the same as those in Example 1, please refer to Example 1.

[0080] Example 5 The difference from Example 1 is that in step S1, the annealing temperature during the nitration process is 800° C. The other steps are basically the same as those in Example 1, please refer to Example 1.

[0081] Example 6 The difference from Example 1 is that in step S2, 500 g of the oxide precursor is weighed and uniformly mixed with 233.8 g of lithium carbonate and 2.56 g of Al2O3 to obtain a positive electrode material having a chemical formula of LiNi 0.60 Co 0.10 Mn 0.30 O2.

[0082] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0083] Example 7 The difference from Example 1 is that in step S2, 500 g of the oxide precursor is weighed and uniformly mixed with 233.5 g of lithium carbonate and 2.53 g of MoO3 to obtain a positive electrode material having a chemical formula of LiNi 0.60 Co 0.10 Mn 0.30 O2.

[0084] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0085] Example 8 The difference from Example 1 is that in step S2, 500 g of the oxide precursor is weighed and uniformly mixed with 233.5 g of lithium carbonate and 2.44 g of SnO2 to obtain a positive electrode material having a chemical formula of LiNi 0.60 Co 0.10 Mn 0.30 O2.

[0086] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0087] Example 9 The difference from Example 1 is that in step S1, a hydroxide precursor Ni 0.50 Co 0.20 Mn 0.30 (OH)2; In step S2, the first stage sintering temperature is 700°C, the sintering time is 6 hours, and the second stage sintering temperature is 930°C, the sintering time is 12 hours. The positive electrode material is obtained, and its chemical formula is LiNi 0.50 Co 0.20 Mn 0.30 O2.

[0088] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0089] Example 10 The difference from Example 1 is that in step S1, the concentration of nitric acid is 1%, the annealing temperature during the nitration process is 600° C., and the other steps are basically the same as Example 1, please refer to Example 1.

[0090] Embodiment 11 The difference from Example 1 is that in step S2, the temperature of the second sintering stage is 950°C, and the other steps are basically the same as Example 1, please refer to Example 1.

[0091] Example 12 The difference from Example 1 is that in step S2, the second sintering time is 10 hours.

[0092] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0093] Embodiment 13 The difference from Example 1 is that in step S2, the second sintering time is 16 hours.

[0094] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0095] Embodiment 14 The difference from Example 1 is that in step S2, the temperature of the second sintering stage is 900°C, and the other steps are basically the same as Example 1, please refer to Example 1.

[0096] Embodiment 15 The difference between this embodiment and embodiment 1 is that in step S1, a hydroxide precursor Ni 0.68 Co 0.10 Al 0.22 (OH)2; in step S2, the first stage sintering temperature is 500°C, the sintering time is 5h, the second stage sintering temperature is 900°C, the sintering time is 10h. The positive electrode material is obtained, and its chemical formula is LiNi 0.68 Co 0.10 Al 0.22 O2.

[0097] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0098] Example 16 The difference between this embodiment and embodiment 1 is that in step S2, WO3 is not added, and in step S3, only the substrate is crushed without coating treatment to obtain the positive electrode material.

[0099] Embodiment 17 The difference between this embodiment and embodiment 1 is that in step S2, the temperature of the second sintering stage is 920°C and the sintering time is 18 hours. The other steps are basically the same as those in embodiment 1, please refer to embodiment 1.

[0100] Embodiment 18 The difference between this embodiment and embodiment 1 is that: in step S1, the annealing temperature during the nitration process is 800° C. and the annealing time is 4 hours. The other steps are basically the same as those in embodiment 1, please refer to embodiment 1.

[0101] Comparative Example 1 Step S1, the hydroxide precursor Ni 0.60 Co 0.10 Mn 0.30 (OH)2 is placed in a nitric acid atmosphere with a concentration of 2% and subjected to nitration annealing treatment to obtain an oxide precursor; the annealing temperature is 500°C, the heating rate is 1.5°C / min, and the holding time is 7h.

[0102] Step S2, weigh 500g of the above oxide precursor, 237.8g of lithium carbonate and 2.25g of Al2O3, mix them evenly, and place the mixture in an oxygen atmosphere furnace for sintering to obtain a positive electrode material matrix; wherein the sintering temperature is 950°C and the sintering time is 18h.

[0103] Step S3, crushing the positive electrode material matrix, weighing 300g of the crushed material and 0.25g of TiO2, and evenly mixing them, and sintering the mixture in an oxygen atmosphere furnace to obtain a positive electrode material; wherein the sintering temperature is 450°C, the sintering time is 8h, and its chemical formula is LiNi 0.60 Co 0.10 Mn 0.30 O2.

[0104] Comparative Example 2 Step S1, the hydroxide precursor Ni 0.60 Co 0.10 Mn 0.30 (OH)2 was placed in a nitric acid atmosphere with a concentration of 1% and subjected to nitration annealing treatment to obtain an oxide precursor; the annealing temperature was 850°C, the heating rate was 1.5°C / min, and the holding time was 7h.

[0105] Step S2, weigh 500g of the above oxide precursor, 237.8g of lithium carbonate and 2.25g of Al2O3, mix them evenly, and place the mixture in an oxygen atmosphere furnace for sintering to obtain a positive electrode material matrix; wherein the sintering temperature is 950°C and the sintering time is 18h.

[0106] Step S3, crushing the positive electrode material matrix, weighing 300g of the crushed material and 0.25g of TiO2, and evenly mixing them, and sintering the mixture in an oxygen atmosphere furnace to obtain a positive electrode material; wherein the sintering temperature is 450°C, the sintering time is 8h, and its chemical formula is LiNi 0.60 Co 0.10 Mn 0.30 O2.

[0107] Comparative Example 3 Step S1, the hydroxide precursor Ni 0.60 Co 0.10 Mn 0.30 (OH)2 is placed in a 3% nitric acid atmosphere for nitration annealing to obtain an oxide precursor; the annealing temperature is 200°C, the heating rate is 1.5°C / min, and the holding time is 7h.

[0108] Step S2, weigh 500g of the above oxide precursor, 237.8g of lithium carbonate and 2.25g of Al2O3, mix them evenly, and place the mixture in an oxygen atmosphere furnace for sintering to obtain a positive electrode material matrix; wherein the sintering temperature is 950°C and the sintering time is 18h.

[0109] Step S3, crushing the positive electrode material matrix, weighing 300g of the crushed material and 0.25g of TiO2, and evenly mixing them, and sintering the mixture in an oxygen atmosphere furnace to obtain a positive electrode material; wherein the sintering temperature is 450°C, the sintering time is 8h, and its chemical formula is LiNi 0.60 Co 0.10 Mn 0.30 O2.

[0110] Comparative Example 4 Step S1, the hydroxide precursor Ni 0.60 Co 0.10 Mn 0.30 (OH)2 is placed in an oxygen atmosphere and subjected to oxidation annealing to obtain an oxide precursor; the annealing temperature is 500°C, the heating rate is 1.5°C / min, and the holding time is 7h.

[0111] Step S2, weigh 500g of the above oxide precursor, 237.8g of lithium carbonate and 2.25g of Al2O3, mix them evenly, and place the mixture in an oxygen atmosphere furnace for sintering to obtain a positive electrode material matrix; wherein the sintering temperature is 950°C and the sintering time is 18h.

[0112] Step S3, crushing the positive electrode material matrix, weighing 300g of the crushed material and 0.25g of TiO2, and evenly mixing them, and sintering the mixture in an oxygen atmosphere furnace to obtain a positive electrode material; wherein the sintering temperature is 450°C, the sintering time is 8h, and its chemical formula is LiNi 0.60 Co 0.10 Mn 0.30 O2.

[0113] Comparative Example 5 Step S1, the hydroxide precursor Ni 0.60 Co 0.10 Mn 0.30 (OH)2 is placed in a 3% nitric acid atmosphere for nitration annealing to obtain an oxide precursor; the annealing temperature is 200°C, the heating rate is 1.5°C / min, and the holding time is 7h.

[0114] Step S2, weigh 500g of the above-mentioned oxide precursor, mix it evenly with 237.8g of lithium carbonate and 2.25g of WO3, and place the mixture in an oxygen atmosphere furnace for sintering to obtain a positive electrode material matrix; wherein, the sintering temperature of the first stage is 550°C, the sintering time is 6h, the sintering temperature of the second end is 920°C, and the sintering time is 12h.

[0115] Step S3, crushing the positive electrode material matrix, weighing 300g of the crushed material and 0.25g of TiO2, and evenly mixing them, and sintering the mixture in an oxygen atmosphere furnace to obtain a positive electrode material; wherein the sintering temperature is 450°C, the sintering time is 8h, and its chemical formula is LiNi 0.60 Co 0.10 Mn 0.30 O2.

[0116] The following method was used to perform performance tests on the positive electrode materials obtained in the above Examples 1-18 and Comparative Examples 1-5.

[0117] 1. Unit cell volume and unit cell parameters: The XRD diffractometer was used to test in the range of 10°-70° at 1° / min and a step size of 0.005°; the tested XRD image was then subjected to Rietveld refinement using GASA software, with the refinement standard being RWP < 3%; after refinement, the unit cell volume and unit cell parameters c and a information can be obtained in the unit cell parameter interface of the GSAS software.

[0118] 2. Test of free nitrate ion content in positive electrode material: (1) Weigh approximately 0.7 g of sample into a 70 mL beaker, accurate to 0.0001 g.

[0119] (2) Accurately measure 50 mL of ultrapure water in a 50 mL volumetric flask. First, add a small amount of ultrapure water (about 7 mL) to the sample. Stir evenly with a glass rod and then add the remaining ultrapure water. Stir evenly and then ultrasonicate for 3 minutes. Let it stand for about 17 minutes to allow the sample to settle.

[0120] (3) Use a 1 mL sterile syringe to draw the sample supernatant, inject it into the instrument through a disposable filter head, and then test it; ion chromatograph model: Thermo Scientific Dionex ICS-6000.

[0121] (4) Chromatographic setting conditions: eluent concentration: 25 mmol / L; eluent flow rate: 0.3 mL / min; column temperature: 30 ± 1 °C; detection cell temperature: 35 ± 1 °C; suppressor current: 26 mA; chromatographic column: anion exchange column (4*250 mm, AS11-HC).

[0122] (5) Data acquisition: After the baseline is stable (the signal value change is less than 0.1 μS / 20 min), use a 1 mL syringe to draw 1 mL of anion mixed solution (supernatant), click data acquisition, and the analysis will begin.

[0123] (6) Calculation of results: The calculation formula is Xi = Ci * V / M, where Xi is the content of element i in the sample, in mg / kg; Ci is the concentration of element i in the sample solution, in mg / L; V is the volume of the sample solution, in mL; M is the mass of the sample, in g. The mass content of nitrate ions is obtained by converting the calculation formula.

[0124] 3. The present invention uses Malvern laser particle size tester MS 3000 to test the particle size of the positive electrode material.

[0125] 4. The test method for the tap density ρ1 of the positive electrode material is as follows: Dandong Better BT-303 was used to test the compacted density: vibration rate 3000 times / min, vibration time 1min, vibration amplitude 3mm±0.1mm.

[0126] 5. The test method for the compaction density ρ2 of the positive electrode material powder is as follows: Using the American Carver 4350 tester, 1g of sample was weighed and placed in a mold, pressed with a pressure of 6t for 30s. After pressing, the height was tested and the compacted density was calculated.

[0127] 6. The test method for the specific surface area S1 of the positive electrode material is as follows: the specific surface area of ​​the material is tested using the McAb 3020 nitrogen adsorption method.

[0128] Finished product pretreatment: weigh the mass of the empty sample tube m1; take 3g of sample, vacuum degas at 300℃ for 1h, and weigh the mass of the sample tube m2 after cooling; sample mass m=m2-m1.

[0129] Sample testing: The sample tube is placed in liquid nitrogen, and the nitrogen adsorption capacity V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm.

[0130] The isothermal adsorption curve was fitted, and the monolayer saturated adsorption capacity Vm was calculated according to the slope and intercept; then the specific surface area was calculated according to Vm.

[0131] 7. Test of standard deviation of Ni, Co and Mn content: The cross-section samples were prepared by using a Hitachi ion cutting instrument, and then the single crystal particle cross-section field was selected using a Hitachi S4800 scanning electron microscope. EDS was then used to scan the cathode material precursor or single crystal cathode material in the field of view at a magnification of 3K at 10 randomly selected points (no less than 3 points in the core and the surface) to test the Ni, Co, and Mn contents of the cathode material precursor or cathode material. The standard deviation and range of the mass content of each element Ni, Co, and Mn were statistically analyzed to characterize the uniformity of the distribution of Ni, Co, and Mn elements.

[0132] 8. Test of free lithium content in positive electrode materials: The test was conducted using the Mettler Toledo G20S equipment. 5 g of the positive electrode active material powder was weighed and added to a 150 ml beaker. 100 ml of pure water was weighed and poured into the beaker and a magnetic stirrer was added. The beaker was sealed with a sealing film. The solution was stirred at a rate of 400 r / min for 5 min. The stirred solution was poured into a suction cup and filtered for 30 s to obtain a filtrate. The equipment was turned on to set the parameters. 0.07 mol / L hydrochloric acid solution was used for titration. 20 mL was taken and the volume was fixed to 40 mL for testing. The titration end point was determined by the potential jump during the reaction, and its content was calculated. The mass content of free lithium was obtained by conversion.

[0133] 9. Test of the main element content in the positive electrode material: Tested using ICPoptima2100DV equipment. Dissolve 0.4g of powder sample of each example in 10ml of aqua regia in a conical flask. The bottle is covered with a watch glass and heated on a hot plate at 250°C for 20min until the sample is completely dissolved. After cooling to room temperature, the solution and rinse water in the conical flask are transferred to a 100ml volumetric flask. After that, fill the volumetric flask with deionized water until the 100mL mark and then completely homogenize. Take out an appropriate amount of solution by pipette and transfer it to a 100ml volumetric flask for the second dilution. At this time, fill the volumetric flask with internal standard and 2% nitric acid until the 100mL mark and then homogenize. Finally, the solution is used for ICP measurement to obtain the contents of Li, Ni, Co, Al, etc.

[0134] 10. Battery production and performance testing: The positive electrode material was mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, and NMP (N-methylpyrrolidone) was added to make a uniform slurry. The slurry was evenly coated on aluminum foil and placed in a 100°C oven for drying for 12 hours. After drying, it was rolled at a pressure of 10 MPa and cut into circular pole pieces with a diameter of 14 mm. The negative electrode used a Li metal sheet with a diameter of 14 mm. The lithium-ion battery was assembled according to the CR2025 button battery in industry. The diaphragm was Cellgard diaphragm, and the electrolyte used an equal amount of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1 mol / L LiPF6 as the electrolyte. The positive pole piece, diaphragm, negative pole piece and electrolyte were assembled into a button battery in an Ar gas glove box with a water content and an oxygen content of less than 0.5 ppm.

[0135] Capacity test system: The blue electric test system is used for electrical performance testing (charge and discharge voltage is 3.0~4.3V, temperature condition is 25℃), 0.1C charging, 0.1C discharging, constant voltage cut-off current is 0.005C, 0.1C discharge capacity is measured, and 0.1C discharge capacity is converted to 0.1C discharge gram capacity mAh / g and first-cycle coulomb efficiency. The blue electric test system is used for electrical performance testing (charge and discharge voltage is 3.0~4.3V, temperature condition is 25℃), 1C charging, 1C discharging, constant voltage cut-off current is 0.005C, 1C discharge capacity is measured, and 1C discharge capacity is converted to 1C discharge gram capacity mAh / g. The rate performance is the ratio of 1C discharge gram capacity to 0.1C discharge gram capacity.

[0136] Cycle test system: At 25°C and a charge and discharge voltage of 3.0-4.3V, after 50 cycles of 0.5C / 1C charge and discharge, the final capacity retention rate after 50 cycles is the cycle performance.

[0137] The corresponding test results of the positive electrode materials of Examples 1-18 and Comparative Examples 1-5 are shown in Tables 1 and 2 below.

[0138] Table 1 Table 2 It can be seen from Table 1-2 that in Examples 1-18, the positive electrode materials all have excellent rate and cycle performance, with a 1C / 0.1C rate ≥87%, an initial efficiency ≥88.1%, and a cycle retention rate ≥97.1% after 50 cycles of 1C / 0.1C, and all maintain a relatively high capacity. This is mainly because, in Examples 1-18, by regulating the corresponding parameters in the nitration annealing process, the content of free nitrate ions in the positive electrode material can be regulated to 10ppm~100ppm. During the first charge and discharge process, the free nitrate ions in the positive electrode material will induce the formation of a Li2O stable interface protective layer on the surface of the material. The protective layer has high chemical stability, can remain inert under high voltage, effectively isolate the electrolyte, and reduce the occurrence of side reactions; at the same time, by regulating the temperature and time of the second-stage sintering, the crystals in the positive electrode material can meet the following requirements: unit cell volume V<102.3Å 3 , the unit cell parameters a≤2.8790 Å, c≤14.2550 Å, so that the positive electrode material has a stable crystal structure, and the distance between atoms or ions in the unit cell is short, which enhances the interaction force between atoms or ions (such as Coulomb force, van der Waals force, etc.), thereby further improving the cohesive energy of the crystal, thereby reducing the volume change during the charge and discharge process, thereby improving the cycle stability.

[0139] Comparative Examples 1-5 Compared with Example 1, the sintering conditions were adjusted, and high temperature sintering was adopted throughout the process. The unit cell volume V of the formed crystals was greater than 102.3 Å. 3 , which reduces the strength and toughness of the lattice, making it easy for the positive electrode material to have lattice defects when subjected to alternating stress, causing particle microcracks, which may become sensitive points for electrochemical corrosion, increase the probability of side reactions with the electrolyte, and affect the cycle life of the battery. Therefore, compared with Examples 1-18, the cycle retention rate of Comparative Example 1-5 is significantly reduced (about 96%).

[0140] Specifically, compared with Comparative Example 1, the annealing temperature of Comparative Example 2 is too high (850°C), so that the content of free nitrate ions in the positive electrode material is only 2ppm (less than 10ppm), which does not reach the reaction concentration of the interface protection layer. The thickness and density of the CEI film may not meet the requirements for effective protection of the positive electrode, and there are many side reactions, thereby reducing the capacity and electrical performance of the battery. Compared with Comparative Example 1, the annealing temperature of Comparative Example 3 is too low, so that the content of free nitrate ions in the positive electrode material reaches 105ppm (exceeding 100ppm). Excessive free nitrate ions will consume more Li + , thereby reducing the capacity and electrical performance of the battery. At the same time, a thicker CEI film will be generated, increasing the internal resistance of the battery, resulting in increased energy loss of the battery during the charge and discharge process, and reducing the efficiency of the battery. The positive electrode material in Comparative Example 4 does not contain free nitrate ions, and will not induce the formation of a CEI film on the surface of the material. Therefore, the capacity and electrical performance of the battery are poor. Although the cell volume and cell parameters of the positive electrode material in Comparative Example 5 meet the requirements, the content of free nitrate ions in the material does not meet the above requirements. During the charge and discharge process, it is difficult to form an effective interface protection layer on the surface of the material, and the cycle performance of the battery is poor.

[0141] in addition, Figure 3 This is the Li element spectrum obtained by XPS characterization of the positive electrode material of Example 1 after the first charge and discharge; Figure 4 This is the Li element spectrum obtained by XPS characterization of the positive electrode material prepared in Comparative Example 2 after the first charge and discharge. Figure 3-4 As shown, after the first charge and discharge of the battery prepared from the positive electrode material, the free nitrate content in the positive electrode material of Comparative Example 2 is 2, and in the spectrum obtained by XPS characterization, the main component of the solid electrolyte film on the surface of the positive electrode material is ROCO2Li, which further illustrates that Li2O is not formed in Comparative Example 2. However, the positive electrode material of Example 1 has an appropriate amount of free nitrate, and Li2O is induced to form on the surface of the positive electrode material after the first charge and discharge.

[0142] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A positive electrode material, characterized in that: The unit cell volume V of the cathode material is less than 102.3 Å 3 ; The unit cell parameters of the positive electrode material are a≤2.8790 Å, c≤14.2550 Å; the content of free nitrate ions in the positive electrode material is N1, wherein 10ppm≤N1≤100ppm.

2. The positive electrode material according to claim 1, characterized in that The content of free lithium ions in the positive electrode material is N2, wherein 300ppm≤N2≤450ppm.

3. The positive electrode material according to claim 1, characterized in that The content N1 of the free nitrate ions is 40ppm~70ppm.

4. The positive electrode material according to claim 1, characterized in that The unit cell volume satisfies: 101.448 Å 3 <V<102.3 Å 3 , the unit cell parameters satisfy: 2.8737 Å≤a≤2.8790 Å; 14.1855 Å≤c≤14.2550 Å.

5. The positive electrode material according to claim 1, characterized in that The general formula of the positive electrode material is as follows: Li x Ni a Co b M c N d O2, M includes at least one of Mn and Al, and the N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Sn, Mo, W, Sb, Ta, Sn, Ga and Y, wherein 0.98≤x≤1.1, 0.50≤a≤0.70, 0.06≤b≤0.12, 0.20<c≤0.32, 0<d≤0.10, a+b+c+d=1.

6. The positive electrode material according to claim 1, characterized in that The cross-section of the positive electrode material was observed with a scanning electron microscope, and 10 points were randomly selected from the cross-section of the positive electrode material for EDS point scanning to test the Ni, Co, and Mn contents. In the EDS spectrum results of the positive electrode material, the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material was 0.001~0.

03.

7. The positive electrode material according to any one of claims 1 to 6, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The volume distribution median particle size D50 of the positive electrode material is 3.5 μm to 4.1 μm; (2) The specific surface area of ​​the positive electrode material is 0.7 m 2 / g ~1.0 m 2 / g; (3) The tap density ρ1 of the positive electrode material is 1.8-2.2 g / cm 3 ; (4) The powder compaction density ρ2 of the positive electrode material is 3.00~3.50 g / cm 3 .

8. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal positive electrode material, and the average particle size of primary particles of the positive electrode material is 1 μm to 5 μm.

9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: The invention comprises an electrode assembly, wherein the electrode assembly comprises a positive electrode material, a separator and a negative electrode plate, wherein the separator is arranged between the positive electrode plate and the negative electrode plate, and the positive electrode plate comprises the positive electrode material as claimed in any one of claims 1 to 8.